2019
DOI: 10.15407/ukrbotj76.02.101
|View full text |Cite
|
Sign up to set email alerts
|

The genus Lichenoconium (Lichenoconiaceae, Ascomycota) in Ukraine

Abstract: Revision of Ukrainian Lichenoconium specimens is provided. This genus is characterized by immersed to semiimmersed black globose conidiomata, phialidic hyaline conidiogenous cells and olive to brown simple conidia. Seven species of the genus are reported from the territory of Ukraine. These are L. aeruginosum, L. erodens, L. lecanorae, L. lichenicola, L. pyxidatae, L. usneae and L. xanthoriae. These species were found on thalli and apothecia of 18 different genera of lichens. Lichenoconium aeruginosum, L. lich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…Physcia stellaris is a new host species. This species was reported only from the steppe zone of Ukraine (Darmostuk andKhodosovtsev 2017, Khodosovtsev et al 2019b). This record is new for the forest-steppe zone.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Physcia stellaris is a new host species. This species was reported only from the steppe zone of Ukraine (Darmostuk andKhodosovtsev 2017, Khodosovtsev et al 2019b). This record is new for the forest-steppe zone.…”
Section: Resultsmentioning
confidence: 97%
“…Katherinomyces cetrariae was described on Cetraria aculeata from Kherson region . Further research has shown that the species is not host specific and can infect other Parmeliaceae species as well as Lecidea fuscoatra and Rhizoplaca chrysoleuca (Darmostuk andKhodosovtsev 2019, Zhurbenko et al 2020).…”
Section: Katherinomyces Cetrariae Khodosmentioning
confidence: 99%
See 1 more Smart Citation
“…This coelomycetes fungus most likely common, but not frequently collected. Confirmed records are known only from Kherson region [DARMOSTUK, 2019]. New for the Mykolaiv region.…”
Section: Lichenochora Obscuroides (Linds) Triebel and Ramboldmentioning
confidence: 99%
“…& Syd. та Lichenostigma Hafellner (Kondratyuk, 2005;Pirogov et al, 2014;Darmostuk, 2016Darmostuk, , 2019.…”
Section: вступmentioning
confidence: 99%